Analyzing the Measurement Equivalence of a Translated Test in a Statewide Assessment Program - Carvajal-Espinoza, Jorge (2016)
When tests are translated into one or more languages, the question of the equivalence of items across language forms arises. This equivalence can be assessed at the scale level by means of a multiple group confirmatory factor analysis (CFA) in the context of structural equation modeling. This study examined the measurement equivalence of a Spanish translated version of a statewide Mathematics test originally constructed in English by using a multi-group CFA approach. The study used samples of native speakers of the target language of the translation taking the test in both the source and target language, specifically Hispanics taking the test in English and Spanish. Test items were grouped in twelve facet-representative parcels. The parceling was accomplished by grouping items that corresponded to similar content and computing an average for each parcel. Four models were fitted to examine the equivalence of the test across groups. The multi-group CFA fixed factor loadings across groups and results supported the equivalence of the two language versions (English and Spanish) of the test. The statistical techniques implemented in this study can also be used to address the performance on a test based on dichotomous or dichotomized variables such as gender, socioeconomic status, geographic location and other variables of interest.